Reflections on Viral Poetry “Paskah” on the Existence of Indonesian Religious Diversity - Achmad Muhajir Muhajir (Yayasan Ilomata, 2021)
Plurality is a necessity in life, especially in religious life. Toleransih or atsamuh which is embodied in the Medina Charter, is a teaching in the context of carrying out a hydrogen community life, especially in religion, so that there is peace in social life. The existence of a viral poem about